Incidence of Helicobacter Pylori in upper gastrointestinal lesion - Vikas Kumar; B. P. Nag; Pallavi Anand; Narayani Joshi; Renu Jain (International Journal of Medical Research and Review, 2018)
Introduction: Helicobacter pylori are gram-negative bacillus. It is noninvasive and live in gastric mucus, with the small proportion of bacteria adherent to the mucosa. Its spiral shape and flagella render Helicobacter pylori motile in mucus environment. Helicobacter pylori is an important pathogen in human causing chronic gastritis and playing a major role in the development of peptic ulcers and gastric cancer.Material and Methods: Study was conducted in Mahatma Gandhi Medical College and hospital, Jaipur (from Jan 2014 to March 2015). 57 Gastrointestinal biopsies were taken who have symptom of dyspepsia. All biopsies taken from different sites were brought in 10%buffered formalin. After overnight fixation in formalin, the tissues were processed in automated tissue processor for dehydration, clearing, and paraffin embedding. Section were cut in rotary microtome at 4 micrometer thickness. The section was stained for Hematoxylin and Eosin stain and Geimsa overnight stain.Result: The present studyincluded 57 cases of upperGIT biopsies (gastro esophageal duodenal biopsies). The incidence of Helicobacter Pylori was seen with chronic gastritis in our study.Conclusion: H.pyloriareetiologically associated with chronic active gas triti s, duodenal ulcer, gastric ulcer, primarygastric B-cell lymphoma or mucosalassociated lymphoid type lymphoma (MALT lymphoma) and gastric adenocarcinoma. Helicobacter pylori induced chronic gas trit is were encountered in 16(47.22%) casesofthe presentstudy. Overnight Giemsa stain was done on all the patients and a histopathological diagnosis was made along with the study of the incidence of Helicobacterpylori positivity in all these patients.